Ameliorative effect of epigallocatechin gallate on sodium fluoride induced oxidative stress mediated metabolism in rat - Pandiyan, Thanga; Prabu, Milton (International Journal of Pharmacology and Toxicology, 2014)
Background: The present study was designed to examine the ant hyperglycemic and antihyperlipidemic effect of Epigallocatechin gallate (EGCG) on fluoride induced oxidative changes in the metabolisms of rats. Methods: The control group received the vehicles only. EGCG alone treated group received the EGCG orally at a dose of 40mg/kg in 10% tween 80 for 4 weeks. The Fl treated group received NaF (25 mg/kg) orally in saline for 4weeks. EGCG + Fl treated group received the EGCG at a dose of 40mg/kg/bw along with NaF. Results: The levels of serum SGOT, SGPT, ALP, ACP and plasma glucose, G6PD, cholesterol, triglycerides, free fatty acids, phospholipids, low density lipoprotein, very low density lipoprotein were significantly increased in fluoride intoxicated rats. Furthermore, a significant increase HMG CoA with decreased glycogen, hexokinase, total protein, albumins, high density lipoprotein, lipoprotein lipase, and lecithin cholesterol acyl transferase was observed in fluoride treated rats with altered histological changes. Pre-oral administration of EGCG at a dose of 40 mg/kg bw to fluoride intoxicated rats for a period of 28 days resulted in a significant reduction in the cholesterol, triglycerides, free fatty acids, phospholipids, low density lipoprotein, very low density lipoprotein, and elevation of high density lipoprotein with hexokinase. Moreover, lipoprotein lipase, lecithin cholesterol acyl transferase, total protein, and albumins were also increased with decreased serum markers and HMG CoA after EGCG treatment. The histological findings of liver also significantly improved with EGCG pretreatment. Conclusions: These results indicate that the natural dietary antioxidant EGCG showed significant protective effect against Fl- induced oxidative stress mediated metabolic alternations in rats. This may be due to its antihyperlipidemic and ant hyperglycemic property; it will provide an accessible and cheap traditional medicine source for treatment of Fl mediated environmental and occupational ailments. Keywords: EGCG, Fluoride, Metabolisms, Lipids, Anti-Hyperlipidemia ROS, Rat.